TYPE II CENSORED EXPONENTIAL DISTRIBUTION FOR ESTIMATING SURVIVAL AND LIFE EXPECTANCY IN BLADDER CANCER PATIENTS - Idrus Syahzaqi; Ardi Kurniawan; Nazwa Salsabila; Dinar Rahma Fauzia; Diah Ayu Nofitasari (Pena Cendekia Insani, 2026)
Bladder cancer incidence and mortality continue to rise, yet global studies on bladder cancer survival prediction remain dominated by nomogram and Cox regression-based approaches overlooking Type II censoring. Using secondary data from 80 bladder cancer patients (48 uncensored, 32 Type II censored) from a public cBioPortal repository, this study applied the Type II censored exponential distribution, selected for its memoryless property and constant hazard rate, to estimate the survival function, hazard function, confidence interval, and Mean Time to Failure (MTTF). Descriptive statistics, a goodness-of-fit test, and maximum likelihood estimation were applied. The data followed an exponential distribution with a mean survival time of 33.95 months, an estimated parameter of 38.01 months, a hazard rate of 0.026, and an MTTF of 38.02 months, with a 95% CI of 29.35-51.56 months. These findings offer preliminary insight relevant to clinical decision-making and SDG Target 3.4 on reducing premature mortality from non-communicable diseases.